CHALLENGES AND SOLUTIONS IN MEETING LEGAL AND HALAL REQUIREMENTS FOR FOOD BUSINESSES - Mahliza, Erfida; Bancin, Nurbaiti; Fadillah, Revi; Akhyar, Zulfadli (LEX SOCIETAS: Journal of Law and Public Administration, 2025)
This study discusses the importance of halal certification in the food industry in Indonesia, particularly for Micro, Small, and Medium Enterprises (MSMEs). Although halal certification has become an urgent need for consumers, many businesses face challenges such as high costs, lack of understanding of regulations, and procedural complexity. Clear and transparent information about halal products is essential to help consumers make informed decisions. Therefore, more intensive educational efforts, collaboration among stakeholders, and the digitization of certification processes are needed to improve accessibility and understanding of halal products, thereby promoting the growth of the food industry in accordance with halal principles.